Analisis Kinerja Usahatani Perkebunan Kelapa Sawitrakyat Dengan Pola Kemitraan (Studi Kasus Polakemitraan Petani Dengan PT. Merbau Jaya Indah Raya Di Kabupaten Konawe Selatan Provinsi Sulawesi Tenggara) - Rahmat Agung (Program Studi Agribisnis Universitas Sumatera Selatan, 2023)
Abstract This study aims to determine the implementation of the partnership model and the partnership relationship of oil palm plantations to the income of plasma farmers at PT. Merbau Jaya Indah Raya, South Konawe Regency. Determination of company informants as many as 2 people using a non-probability sampling technique with a judgment approach. While determining partner farmer informants using purposive, namely as many as 20 people. The results showed that the partnership model between plasma farmers and PT. Merbau Jaya Indah Raya in Konawe Selatan Regency is a nucleus-plasma partnership model managed by a nucleus company where the farmer provides land and labor, while the company provides production facilities and provides technical guidance from cultivation to harvest and guarantees market certainty to farmers. The average income received by land owners who partner with PT. Merbau Jaya Indah Raya is Rp. 14,429,008/ year.